Biosurfactant-producing yeasts widely inhabit various vegetables and fruits. Issue 3 (4th March 2014) - Konishi, Masaaki; Maruoka, Naruyuki; Furuta, Yoshifumi; Morita, Tomotake; Fukuoka, Tokuma; Imura, Tomohiro; Kitamoto, Dai
Abstract: The isolation of biosurfactant-producing yeasts from food materials was accomplished. By a combination of a new drop collapse method and thin-layer chromatography, 48 strains were selected as glycolipid biosurfactant producers from 347 strains, which were randomly isolated from various vegetables and fruits. Of the producers, 69% were obtained from vegetables of the Brassica family. Of the 48 producers, 15 strains gave relatively high yields of mannosylerythritol lipids (MELs), and were identified as Pseudozyma yeasts. These strains produced MELs from olive oil at yields ranging from 8.5 to 24.3 g/L. The best yield coefficient reached 0.49 g/g as to the carbon sources added. Accordingly, MEL producers were isolated at high efficiency from various vegetables and fruits, indicating that biosurfactant producers are widely present in foods. The present results should facilitate their application in the food and related industries. Graphical abstract: : Mannosylerythritol lipids (MELs) producers were isolated from food materials by an improved drop collapse method and thin-layer chromatography.